Pengaruh Keterampilan Usahatani Cabai terhadap Produksi di Subak Tianyar Kaja, Kecamatan Sukawati, Kabupaten Gianyar - ADNYANA, I NENGAH SURATA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022, 2022)
The Effect of Chili Farming Skills on Production in Subak Tianyar Kaja, Sukawati District, Gianyar Regency.  Farming is an activity that requires good skills. Skills will affect the productivity of an activity. One of the activities that require intensive skills to increase yields is chili farming. Chili commodities often experience fluctuations in production and inflation of a nation's economy. Subak Tianyar Kaja has the potential for chili development because it is supported by institutional factors, geographical location of the land, fertility and good irrigation. The objectives of this study were (1) to analyze the chili farming subsystem skills on production in Subak Tianyar Kaja, Guwang Village, Sukawati District, Gianyar Regency; (2) analyze the factors that constrain farmers in increasing chili production in Subak Tianyar Kaja, Guwang Village, Sukawati District, Gianyar Regency. The research location was taken purposively, the population was 88 farmers, the sample was taken by simple random sampling taken as much as 30% of the population, namely 27 farmers. The results showed that (1) the chili farming subsystem skills in increasing production which consisted of land preparation, nursery techniques, nursery seed maintenance, mulch installation, seed procurement, seed treatment, planting, maintenance and harvest handling got an average value of 2.45. (51.85%) with low category; (2) the factors that become obstacles for farmers in increasing chili production which include the ability to access technology, grow cooperative networks, hold meetings and capitalize on an average score of 2.29 (45.92%) with a low category. The conclusions of this study are (1) the chili farming subsystem skills on average get an average value of 2.45 (51.85%) which is classified as low category for chili production in Subak Tianyar Kaja, Guwang Village, Sukawati District, Gianyar Regency; (2) the factors that become obstacles in increasing chili production get an average value of 2.29 (45.92%) with a low category of chili production in Subak Tianyar Kaja, Guwang Village, Sukawati District, Gianyar Regency. Suggestions that can be given (1) are farmers' skills which include nursery seed maintenance, mulching mulch, seed treatment, planting, and maintenance of chili plants need to be improved in an effort to increase chili production; (2) the constraint factors which include the ability to access technology, grow cooperation networks, meeting attendance, and capital need to be improved in their implementation in an effort to increase chili production.